Capecitabine-Induced Ileitis during Neoadjuvant Pelvic Radio-Chemotherapy for Locally Advanced Rectal Cancer: A Case Report with Literature Review - Andrea Brignoli; Eleonora Ferrara; Micol Zannetti; Gianfranco Loi; Laura Forti; Carlo Socci; Alessandro Carriero; Alessandra Gennari; Marco Krengli; Pierfrancesco Franco (Current Oncology, 2023)
We report on a clinical case of capecitabine-induced acute ileitis in a patient treated with pre-operative concurrent chemoradiation with capecitabine for locally advanced rectal cancer and provide a comprehensive literature review. This a rare, but life-threatening, clinical situation, that clinicians should be aware of. Severe persistent diarrhea is the most frequent clinical feature and computed tomography is a valid tool for diagnosis. Conservative management includes capecitabine withdrawal, antidiarrheal therapy and endovenous hydration, together with dietary modifications and broad-spectrum antibiotics. Pelvic irradiation represents an adjunctive risk factor, which may increase the likelihood of occurrence of terminal ileitis. Early recognition and prompt intervention are crucial for successful clinical management.